Affirming the context of instructed SLA: The potential of curricular thinking. (July 2019) - Byrnes, Heidi
Offered as a conceptual and programmatic piece, this article suggests that, due to its explicit educational orientation, the domain of instructed second language acquisition (ISLA) is challenged to align theoretical choices, research preferences, and educational practices in the interest of improving instructed L2 learning. It addresses the current disjuncture by proposing the constructs of 'development' along with 'curricular thinking', particularly when they are informed by complexity theory, in order to accomplish three interrelated goals: first, to specify a given educational context in a manner that allows for principled inquiry into how instructed L2 learning evolves in that setting; second, to affirm and operationalize its longitudinal trajectory in a traceable and actionable manner; and, third, to embed the situated and contingent forms of 'doing teaching' and 'doing learning' within a framework that gives them meaning, value, and significance for long-term development. The article discusses core issues arising from such an approach and briefly exemplifies it with curriculum development in a collegiate foreign language (FL) department. It concludes with a consideration of benefits for ISLA.